Spring Enterprise Recipes A Problem-Solution Approach - Mak, Gary; Long, Josh (Apress : Imprint: Apress, 2010)
The Spring framework is a widely adopted enterprise and general Java framework. The release of Spring Framework 3.0 has added many improvements and new features for Spring development. Written by Gary Mak, author of the bestseller Spring Recipes, and Josh Long, an expert Spring user and developer, Spring Enterprise Recipes is one of the first books on Spring 3.0. This key book focuses on Spring Framework 3.0, the latest version available, and a framework-related suite of tools, extensions, plug-ins, modules, and more-all of which you may want and need for building three-tier Java EE applications. Build Spring enterprise and Java EE applications from the ground up using recipes from this book as templates to get you started, fast. Employ Spring Integration, Spring Batch and jBPM with Spring to bring your application's architecture to the next level. Use Spring's remoting, and messaging support to distribute your application, or bring your application to the cloud with GridGain and Terracotta.